SMALL-SCALE EXPERIMENTS BY SIMPLE APPARATUS TO MEASURE STANDARD AND NON-STANDARD REDUCTION POTENTIAL - Fitriani, Wily
One of the lessons which is studied in Senior High School is electrochemistry, which is quite hard and often generates conceptual mistake among the students, for example reduction potential concept. There are numbers of students which only know reduction potential data which easily found on table without realizing the main concept and how to obtain the data. This thesis was aimed to design experiments with a different approach by using small-scale and simple appparatus to measure standard and non-standard reduction potentials. Small-scale experiments is one of alternative learning method which can be done at schools with limitation in laboratory apparatus and chemicals. The small-scale experiments have advantages that is more economical, efficient, safe, fun and environmentally friendly. In this research, conventional experiments were done with the same condition and chemicals. If silver applied as secondary comparator electrode is obtained difference 0,2 %, while if copper applied as secondary comparator electrode is obtained difference 1,15 %. The results of both experiments were compared to statisticially with Bartlet method and Jandel SigmaStat Statistical Software version 2.0. From the calculations it can be concluded there are no significant differences between the results of small-scale experiments and conventional experiments. Deliverables of this work are experimental modules for students and experimental guides for teachers. The electronic version were placed in an online learning system called Modular Object Oriented Dynamic Learning Environment (MOODLE), to acquire feedback from users. Small-scale experiments hopefully could increase students’ motivations, improve their understanding of concepts and principles, and increase laboratory skills in electrochemistry.